Faktor-Faktor Penentu Produktivitas UMKM Songket - Mayang Efridiyanti; Efni Cerya (Universitas Negeri Padang, 2021)
This study aims to analyze the effect of education, business capital, raw materials and work experience on the productivity of songket MSME in Lima Puluh Kota and Tanah Datar districts. This type of research is descriptive associative. The population in this study were songket MSME entrepreneurs. The sample used was 33 people using saturated samples. The type of data used is primary data. The data collection technique used a questionnaire. The collected data were analyzed using multiple regression analysis. The results of this study indicate that 1) education has a positive and significant effect on the productivity of songket MSME in Lima Puluh Kota and Tanah Datar districts, 2) business capital has a positive and significant effect on the productivity of songket MSME, 3) raw materials positive and significant effect on the productivity of songket MSME, 4) work experience has a positive and significant effect on the productivity of songket MSME.Keywords : produktivity, MSME, educational, bussines capital, raw materials, work experince